Association between vitamin D levels and left ventricular function and NT-proBNP levels among thalassemia major children with iron overload - Leny Ambarwati; Sri Endah Rahayuningsih; Budi Setiabudiawan (Wolters Kluwer Medknow Publications, 2016)
Background: Heart disease is the major cause of death in thalassemia patients. Repeated blood transfusions and hemolysis cause iron overload and also disrupts the hydroxylation and synthesis of vitamin D, causing vitamin D deficiency. Vitamin D deficiency is associated with cardiac dysfunction. Objective The purpose of this study was to determine the association between vitamin D levels and left ventricular function and N-terminal pro-brain natriuretic peptide (NT-proBNP) levels in thalassemia major children with iron overload. Patients and Methods: A cross-sectional study was conducted in March-April 2015 in the thalassemia clinic, Department of Child Health, Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. Thirty-four children with thalassemia were enrolled consecutively. Serum vitamin D and NT-proBNP levels were measured with electrochemiluminescence (ECLIA) method and echocardiography was performed to assess ventricular function. Results: Significant correlations were found between vitamin D levels and left ventricular ejection fraction (LVEF) (r = 0.399, P = 0.019) and fractional shortening (FS) (r = 0.394, P = 0.021). There was also significant correlation between vitamin D and NT-proBNP levels (r = -0.444, P = 0.008). Chi-square analysis also showed a relationship between vitamin D and NT-proBNP (P = 0.019) levels. There was a difference in NT-proBNP levels among thalassemia major children with iron overload (P = 0.020). Post hoc analysis showed that there was a significant difference in NT-proBNP levels between those with vitamin D deficiency and those with normal vitamin D levels (P = 0.012). Conclusion: There is an association between vitamin D and left ventricular function and NT-proBNP levels in children with thalassemia major and iron overload. Vitamin D can be considered in patients with thalassemia having vitamin D deficiency.